The birds of Bukit Tigapuluh, Southern Riau, Sumatra - Finn Danielsen; Morten Heegaard (KUKILA, 1995)
A study was made of the avifauna of the Bukit Tigapuluh area in Riau and Jambi Provinces, Sumatra in July-September 1991. This is the first major study of the lowland bird fauna of mainland Riau in this century. A total of 193 bird species was recorded, including 18 species listed as globally threatened. Extensions to known ranges were made for 26 species of which 25 were new to Riau and 3 to Jambi- Data were also provided on 5 species for which there were no recent Sumatran records: Crestless Fireback Pheasant Lophura erythropthalma. Garnet Pitta Pitta granatina, Striped Wren-babbler Kenopia striata. Large Wren-babbler Napothera macrodactyla and Chestnut-capped Thrush Zoothera interpres. In addition, information on breeding was provided for 51 species, of which 22 species were not previously documented to breed in Sumatra.